Characterization of Pediococcus ethanolidurans CUPV141: A β-D-glucan- and Heteropolysaccharide-Producing Bacterium - Llamas-Arriba, María G.; Pérez-Ramos, Adrián; Puertas, Ana I.; López, Paloma; Dueñas, María T.; Prieto, Alicia (Frontiers in Microbiology, 2018)
Pediococcus ethanolidurans CUPV141 is an exopolysaccharide (EPS)-producing lactic acid bacterium, first isolated from Basque Country cider (Spain). Physicochemical analysis of the EPS synthesized by the bacterium revealed that CUPV141 produces mostly a homopolysaccharide (HoPS), characterized as a 2-substituted (1,3)--D-glucan, together with a small quantity of a heteropolysaccharide (HePS) composed of glucose, galactose, glucosamine and glycerol-3-phosphate. On the contrary, an isogenic strain CUPV141NR, generated by chemical mutagenesis of CUPV141, produced the HePS as the main extracellular polysaccharide and a barely detectable amount of 2-substituted (1,3)-beta-D-glucan. This HoPS is synthesized by the transmembrane GTF glycosyltransferase (GTF), encoded by the gtf gene, which has been previously reported to be located in the pPP2 plasmid of the Pediococcus parvulus 2.6 strain. Southern blot hybridization revealed that in CUPV141 the gtf gene is located in a plasmid designated as pPE3, whose molecular mass (34.4 kbp) is different from that of pPP2 (24.5 kbp). Analysis of the influence of the EPS on the ability of the producing bacteria to adhere to Caco-2 cells indicates that, in contrast to the 2.6 strain, the presence of the HoPS does not potentiate the binding ability of P. ethanolidurans. Moreover, the higher affinity for the human enterocytes of CUPV141NR compared to that of CUPV141, supports that the phosphorylated bacterial HePS improved the interaction between P. ethanolidurans and the eukaryotic cells.